Identifying and antagonizing the interactions between layilin and glycosylated collagens. Issue 4 (21st April 2022) - Glasgow, Jeff E.; Byrnes, James R.; Barbee, Susannah D.; Moreau, Joshua M.; Rosenblum, Michael D.; Wells, James A.
Summary: Layilin is a small type I transmembrane receptor thought to bridge extracellular ligands with the cytoskeleton through its intracellular interactions with the scaffolding protein talin. Recent bulk- and single-cell RNA sequencing experiments have repeatedly found layilin to be highly upregulated in key T cell sub-populations in multiple disease states, suggesting its importance to the adaptive immune response. Despite this prevalence, little is known about layilin's precise role in mediating extracellular interactions or how these interactions can be modulated in disease states. Here we take advantage of layilin's dependence on calcium ions to discover its interactions with highly glycosylated type II, IV, V, and VI collagens. Toward exploring layilin's role in disease, we exploited the Ca 2+ dependence in a differential phage display strategy to engineer species cross-reactive antibodies that block this interaction. Graphical abstract: Highlights: Affinity purification/mass spectrometry shows that layilin binds glycan-rich collagens Calcium ion binding can be leveraged to engineer epitope-specific antibodies Calcium-dependent and -independent antibodies have different binding properties Abstract : C-type lectins (CLECs) mediate numerous cellular and ECM interactions. Glasgow et al. demonstrate that layilin, a CLEC receptor found on exhausted and regulatory T cells, interacts with highly glycosylated collagens. Furthermore, a differential enrichment strategy is developed to bias phage displayed antibody selections toward Ca 2+ -dependent functional binders.